Fructooligosaccharides supplementation: effects on broiler chicken performance, intestinal morphology, microbial community, and stress indicators - P. Phungkeha; P. Tiyaprasertkul; Chanporn Chaosap; Panneepa Sivapirunthep; Y. Ruangpanit; Konkawat Rassmidatta; Ananchai Philatha; K. Srikitkasemwat (International Journal of Agricultural Technology, 2025)
Feeding broilers with different amounts of fructooligosaccharides (FOS) under conditions of higher stocking densities and reused litter did not affect growth performance (p>0.05). However, FOS supplementation improved gut health by increasing villus height to crypt depth ratio. It also promoted the growth of Lactobacillus and reduced the incidence of Escherichia coli. The decrease in heterophils to lymphocytes ratio in FOS-supplemented group indicates a reduction in stress levels.
Keywords: Animal Nutrition and Physiology; Rabbits: Nutrition, Reproduction, Health; Meat and Animal Product Quality